2008
DOI: 10.1634/stemcells.2007-0869
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Embryonic Stem Cell Lines Derived from Nonhuman Primate Parthenotes

Abstract: Monoparental parthenotes represent a potential source of histocompatible stem cells that should be isogenic with the oocyte donor and therefore suitable for use in cell or tissue replacement therapy. We generated five rhesus monkey parthenogenetic embryonic stem cell (PESC) lines with stable, diploid female karyotypes that were morphologically indistinguishable from biparental controls, expressed key pluripotent markers, and generated cell derivatives representative of all three germ layers following in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 37 publications
2
70
0
1
Order By: Relevance
“…Methods for isolation and culture of monkey ESCs from in vitro fertilization, SCNT, and parthenogenetic embryos used in this study were reported previously (Mitalipov et al 2006;Byrne et al 2007;Dighe et al 2008). Briefly, ESCs were grown on feeder layers (mouse embryonic fibroblasts, mEFs) in DMEM/F12 medium with glucose and without sodium pyruvate, supplemented with 1% nonessential amino acids, 2 mM L-glutamine, 0.1 mM b-mercaptoethanol, and 15% FBS at 37°C, 3% CO 2, 5% O 2 , and 92% N 2 .…”
Section: Stem Cells Culturementioning
confidence: 99%
“…Methods for isolation and culture of monkey ESCs from in vitro fertilization, SCNT, and parthenogenetic embryos used in this study were reported previously (Mitalipov et al 2006;Byrne et al 2007;Dighe et al 2008). Briefly, ESCs were grown on feeder layers (mouse embryonic fibroblasts, mEFs) in DMEM/F12 medium with glucose and without sodium pyruvate, supplemented with 1% nonessential amino acids, 2 mM L-glutamine, 0.1 mM b-mercaptoethanol, and 15% FBS at 37°C, 3% CO 2, 5% O 2 , and 92% N 2 .…”
Section: Stem Cells Culturementioning
confidence: 99%
“…Since the expression of GFP and MeCP2 transgenes was driven by the same promoter, the expression of GFP is a good indicator for the expression of MeCP2. Short tandem repeat (STR) genotyping and single-nucleotide polymorphism (SNP) analysis were performed to examine the parental origin of the F1 monkeys [11]. The analysis of 23 STR loci of the 7 XG monkeys confirmed their paternal origin (Supplementary information, Table S1B).…”
mentioning
confidence: 92%
“…Recently, a considerable number of studies has reported similar abnormal karyotypes, with y chromosome deletion observed in SCNT monkey ES cell lines (8), and recurrent genomic instability has been reported in hES cell lines over long-term culture (9). Genomic imprinting is a genetic phenomenon by which certain genes are expressed in a parent-of-origin-specific manner.…”
Section: Discussionmentioning
confidence: 86%